Relationship Between the Level of Knowledge of Covid-19 and The Movement Control Order (MCO) among Patients at Kinarut Health Clinic. - Baddiri, Baidi; Abdullah, Mohd Khairuddin; Musa, Mazlinda; Mamat, Rohani; Makajil, Johari Daud; Duasin, Clarice; Jelemie, Caroline Satu (Universitas Muhammadiyah Surakarta, 2024)
The country has been facing the Covid-19 crisis that has affected the rest of the world in this decade. Numerous approaches and alternatives are implemented by the government to overcome this pandemic either controlled or stopped utterly. In order for the government to succeed, the emphasis on breaking the chain of infection of Covid-19 and the direction of the Movement Control Order (MCO) must be strengthened. Thus, the main goal of this study is to identify the level of patient’s knowledge regarding Covid-19 and Movement Control Order as well as to analyze the relationship between the level of knowledge about Covid-19 and Movement Control Order () among patients who come for treatment at the Kinarut Health clinic. Methodology: This study applies the quantitative research methodology, specifically surveys through questionnaires, whereas the sampling method used is systematic sampling with 200 patients in the Kinarut area. Analysis of instrument evaluation and sampling technique is also discussed in this study. Analysis: The finding showed that the patients' knowledge level about Covid-19 was at a moderate level with a mean value = 3.610, SD = 0.345. The level of knowledge relating to Movement Control Order (MCO) is also at a moderate level with a mean value = 3.610, SP = 0.345. Result: The correlation analysis showed that there is a strong relationship between the level of knowledge about Covid-19 and the level of knowledge of the Movement Control Order, with a correlation value of r = 0.71, p> 0.05. Thus, the results of this analysis show that there is a strong relationship between the variables of the knowledge level of Covid-19 and Movement Control Order in breaking the chain of infection Covid-19, particularly among patients who are living around Kinarut.